2018
DOI: 10.1257/jep.32.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Sources of the Gains from International Trade: Variety, Creative Destruction, and Markups

Abstract: The modern theory of international trade identifies several additional sources of the gains from international trade beyond the gains from traditional comparative advantage. These are the gains from importing new product varieties; the gains from “creative destruction” as the relatively most productive firms expand their output by exporting while the less-productive firms exit; and the gains from competition between firms in different countries, which can lead to reduced markups. Estimates of these various gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 67 publications
4
17
0
2
Order By: Relevance
“…Kehoe and Ruhl (2013) analysed 1900 country pairs and found that increased trade in goods not previously exported is an important factor in overall trade growth. In a recent survey Feenstra (2018) underscores that variety is one of the crucial sources of the gains from international trade, empirically estimated by Broda and Weinstein (2006) for the U.S. and confirmed in a cross-industry multi-country setting by Ossa (2015) .…”
Section: The Literaturementioning
confidence: 92%
“…Kehoe and Ruhl (2013) analysed 1900 country pairs and found that increased trade in goods not previously exported is an important factor in overall trade growth. In a recent survey Feenstra (2018) underscores that variety is one of the crucial sources of the gains from international trade, empirically estimated by Broda and Weinstein (2006) for the U.S. and confirmed in a cross-industry multi-country setting by Ossa (2015) .…”
Section: The Literaturementioning
confidence: 92%
“…Globalization and trade integration can bring about significant improvements in countries' welfare (see, e.g., Costinot andRodríguez-Clare, 2018, andFeenstra, 2018, for a recent discussion). As a case in point, the two decades preceding the Great Recession-and the associated trade collapse-have seen a rapid expansion in trade participation for many developed countries, coupled with substantial improvements in their living standards.…”
Section: Introductionmentioning
confidence: 99%
“…A diferencia de lo que ocurre con la diversificación de exportaciones, existe un importante sustento teórico y empírico respecto de los beneficios de profundizar el comercio internacional. Como ha sido documentado por Feenstra (2018), los beneficios del comercio internacional van más allá de aprovechar las ventajas comparativas, ya que se expande la variedad de productos a la que pueden acceder los consumidores, permite el crecimiento de las empresas más productivas a través de las exportaciones y disminuye los precios mediante la competencia internacional. En términos cuantitativos, Costinot y Rodríguez-Clare (2018) señalan que las ganancias del comercio internacional están en un rango entre 2% y 8% del PIB para el caso de Estados Unidos, pero tales ganancias serían aún mayores para una economía pequeña como la de Chile.…”
Section: Export Diversification: Is Chile Different Fromunclassified
“…La literatura económica analizada sugiere que la política comercial debiese centrarse en potenciar el sector exportador y no en diversificar las exportaciones como un objetivo en sí mismo. En particular, existe sustento teórico y empírico respecto de los beneficios de profundizar el comercio internacional (Feenstra 2018;Costinot y Rodríguez-Clare 2018), así como sobre la efectividad de los programas para facilitar las exportaciones (Munch y Schaur 2018;Volpe y Carballo 2008), mientras que no hay evidencia contundente respecto de los efectos de la diversificación de exportaciones (Cadot, Carrère y Strauss-Kahn 2011, 2013. Además, Besedeš y Prusa (2011) encuentran que el crecimiento de las exportaciones está asociado principalmente con el margen intensivo, es decir, con un aumento en los montos transados en los productos ya exportados, y no con un aumento en la variedad de productos exportados.…”
Section: Discusión: Lineamientos Para Políticas Públicasunclassified